2019
DOI: 10.3390/app9081645
|View full text |Cite
|
Sign up to set email alerts
|

PANDAS: Paediatric Attention-Deficit/Hyperactivity Disorder Application Software

Abstract: Attention-deficit/hyperactivity disorder (ADHD) is a common neuropsychiatric disorder that impairs social, academic and occupational functioning in children, adolescents and adults. In South Africa, youth prevalence of ADHD is estimated as 10%. It is therefore necessary to further investigate methods that objectively diagnose, treat and manage the disorder. The aim of the study was to develop a novel method that could be used as an aid to provide screening for ADHD. The study comprised of a beta-testing phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Another application is PANDAS, which aims to detect children's ADHD quickly through a game. Authors of PANDAS concluded that the model used in their game helped detect ADHD in children with an accuracy of 86.5% and was easy for children to use [11].…”
Section: Mobile Applications For Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Another application is PANDAS, which aims to detect children's ADHD quickly through a game. Authors of PANDAS concluded that the model used in their game helped detect ADHD in children with an accuracy of 86.5% and was easy for children to use [11].…”
Section: Mobile Applications For Learningmentioning
confidence: 99%
“…The recommendation to add more games in the following updates is highlighted because when it compares to the Say-It & Learn application, it has more interactive games focused on improving children's cognitive areas [12]. While the PANDAS application presented an interactive game to measure the WM of children, generating a high value in efficiency and usability [11]. Likewise, in this sense, the badge system, a new module not implemented in the reviewed applications, contributed significantly to children's usability experience and satisfaction, according to the comments received by parents.…”
Section: About the Usability And Satisfaction Of The Mobile Applicationmentioning
confidence: 99%
“…Contributions can focus on sensors, wearable hardware, algorithms, or integrated monitoring systems. We organized the different papers according to their contributions to the main parts of the monitoring and control engineering scheme applied to human health applications, namely papers focusing on measuring/sensing of physiological variables [24][25][26][27][28][29][30][31], contributions describing research on the modelling of biological signals [32][33][34][35][36][37][38], papers highlighting health monitoring applications [39][40][41][42], and finally examples of control applications for human health [43][44][45][46][47][48]. In comparison to biomedical engineering, we envision that the field of human health engineering also covers applications on healthy humans (e.g., sports, sleep, and stress) and thus not only contributes to develop technology for curing patients or supporting chronically ill people, but also for disease prevention and optimizing human well-being more generally.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%
“…The clinical relevance of such a model is that it allows simulation and evaluation of heart activity and dynamics under different types of pacemaker couplings. The study of Mwamba et al [35] contributed to the diagnosis and management of attention-deficit/hyperactivity disorder (ADHD) by developing a tablet-based application (app) software using support vector machine (SVM) approaches from machine learning. Their approach demonstrated that (serious) games in combination with modelling approaches from the field of artificial intelligence can offer a useful tool for first line screening of children for ADHD by their parents and/or teachers.…”
Section: Main Content Of the Special Issuementioning
confidence: 99%